The Influence of Omni-Channel Marketing Environments on Shoppers’ Purchasing Decisions: An Empirical Study on the Mediating Role of PSYCHOGRAPHIC Factors - Praveena, Ms. N. S. Lakshmi; Shankar, Dr. A. Udaya (International Journal of Aquatic Research and Environmental Studies, 2026)
Purpose: The study focused to know the role of Omni-Channel Marketing Environment on the Shoppers Purchase decision with the mediation effect of Psychographic Factors. The study analysed the direct effect of it on the purchase decision of shoppers in Textile segment. Research Methodology: Acc, the study has considered quantitative research approach for the examination of OCE Impact on the shoppers purchase intention with Andrew F Hayes Mediation effect statistical method for the examination of framed objectives. The study considered convenient sampling method and collected the 170 sample. Findings: The results through the stats that significant positive influence have been observed on the buyers’ behaviour by the performance expectancy, social influence, and perceived security as partially mediating factors since they are all fundamental psychographics. Which in turn underlined the impact of psychographics in enhancing the potency of the omni channel marketing strategy on the decisions of consumers. Conclusion: The “omni channel marketing environments are significant influencers of buyers’ purchasing decisions indirectly through direct influences and indirectly through psychographic factors”. The study concludes that investing in a personalized and secure omni channel marketing environment for higher social inter-activeness should be prioritized for higher brand effectiveness in today’s ever-changing retail scenario.